CitSci.org: A New Model for Managing, Documenting, and Sharing Citizen Science Data. - Yiwei Wang; Nicole Kaplan; Greg Newman; Russell Scarpino (PLoS Biology, 2015)
Citizen science projects have the potential to advance science by increasing the volume and variety of data, as well as innovation. Yet this potential has not been fully realized, in part because citizen science data are typically not widely shared and reused. To address this and related challenges, we built CitSci.org (see www.citsci.org), a customizable platform that allows users to collect and generate diverse datasets. We hope that CitSci.org will ultimately increase discoverability and confidence in citizen science observations, encouraging scientists to use such data in their own scientific research.